2011
DOI: 10.1111/j.1567-1364.2011.00773.x
|View full text |Cite
|
Sign up to set email alerts
|

The genome sequence of the wine yeast VIN7 reveals an allotriploid hybrid genome with Saccharomyces cerevisiae and Saccharomyces kudriavzevii origins

Abstract: The vast majority of wine fermentations are performed principally by Saccharomyces cerevisiae. However, there are a growing number of instances in which other species of Saccharomyces play a predominant role. Interestingly, the presence of these other yeast species generally occurs via the formation of interspecific hybrids that contain genomic contributions from both S. cerevisiae and non-S. cerevisiae species. However, despite the large number of wine strains that are characterized at the genomic level, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
2
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 35 publications
6
87
2
2
Order By: Relevance
“…Molecular characterization of wine, beer, or cider yeasts revealed numerous independently formed hybrids between S. cerevisiae and S. kudriavzevii (8,9,22,57,63,64,120,121,164,198), between S. cerevisiae and S. bayanus (60,78,106,133,134,141,146,175,198), and even (triple hybrids) between S. cerevisiae, S. kudriavzevii, and S. bayanus (18,32,62). Such hybrids often exhibit more robust characteristics than the parental strains, such as tolerance to various stresses induced by artificial fermentations (11,174,175,216).…”
Section: Natural Hybrids Between Saccharomyces Sensu Stricto Speciesmentioning
confidence: 99%
“…Molecular characterization of wine, beer, or cider yeasts revealed numerous independently formed hybrids between S. cerevisiae and S. kudriavzevii (8,9,22,57,63,64,120,121,164,198), between S. cerevisiae and S. bayanus (60,78,106,133,134,141,146,175,198), and even (triple hybrids) between S. cerevisiae, S. kudriavzevii, and S. bayanus (18,32,62). Such hybrids often exhibit more robust characteristics than the parental strains, such as tolerance to various stresses induced by artificial fermentations (11,174,175,216).…”
Section: Natural Hybrids Between Saccharomyces Sensu Stricto Speciesmentioning
confidence: 99%
“…1). VIN7 and NT50 have been previously characterized as S. cerevisiae-S. kudriavzevii hybrids (Bradbury et al 2006;Sampaio and Gonc xalves 2008;Borneman et al 2011b), but to our knowledge the wine yeasts NT45 and EPII have not previously been identified as interspecific hybrids. No other interspecific hybrids with any other Saccharomyces species were observed among our set of 83 strains.…”
Section: Interspecific Hybridization and Introgression Eventsmentioning
confidence: 99%
“…Of these, VIN7 and NT50 had been previously identified as such (Bradbury et al 2006;Sampaio and Gonc xalves 2008;Borneman et al 2011b); however, the status of EPII and NT45 as interspecific hybrids is novel. We found that VIN7 is a triploid and contains a complete S. kudriavzevii genome; both observations have been recently confirmed by whole-genome sequencing (Borneman et al 2011b). In contrast, we found that the other three strains have lost many (from 10 to 15) of the S. kudriavzevii chromosomes, similar to previously identified S. cerevisiae-S. kudriavzevii hybrids (Gonzalez et al 2008).…”
Section: Interspecific Hybridization and Introgressionmentioning
confidence: 99%
“…The only assembled genome sequence available for a hybrid wine yeast strain is that of the commercial strain VIN7 (Borneman et al 2012). Analysis showed that VIN7 was an allotriploid, resulting from hybridization between a heterozygous diploid wine-like strain of S. cerevisiae and a haploid, European isolate of S. kudriavzevii ( Figure 1C).…”
Section: Wine Yeast Hybridsmentioning
confidence: 99%